UPN Veteran East Java International Relations Students' Understanding of Tolerance for Worship Between Religious People: Case Study of the 2018 Surabaya Church Bombing - Kurnia Yusuf, Hendrawan; Wardi, Moh. (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This study aims to examine the understanding of International Relations students at the Veteran National Development University in East Java regarding tolerance in interfaith worship. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews with ten students. The focus of this study is on students' understanding in responding to the diversity of worship practices and their attitudes towards the 2018 church bombings in Surabaya. The results show that most students have an inclusive view of freedom of worship and consider acts of intolerance as a threat to social harmony. This understanding is influenced by educational background, media, social environment, and multicultural values acquired on campus. However, it was also found that a small number of students still have limited understanding due to a lack of interfaith knowledge and exposure to issues of intolerance. This study recommends that tolerance education be further enhanced in an applied and contextual manner in higher education settings, in order to strengthen moderate attitudes and respect for differences in religious life in multicultural societies such as Indonesia.